Video laryngoscope: A boon for airway management in severe facial trauma - Shailendra Kumar; Sweta Singh; Nilesh Kumar; Surya Kumar Dube (Wolters Kluwer Medknow Publications, 2016)
We report the use of video laryngoscope for the exchange of orotracheal tube to nasotracheal tube needed for mandibular repair in a case of oromaxillofacial injury.